2016
DOI: 10.1155/2016/9717489
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy Practice Patterns for Management of Patients Undergoing Thoracic Surgeries in India: A Survey

Abstract: Aim. The aim of the current study is to determine the practice patterns of physiotherapists for patients undergoing thoracic surgeries in India. Materials and Methodology. A cross-sectional survey was conducted across India in which 600 questionnaires were sent in emails to physiotherapists. The questionnaire addressed assessment and treatment techniques of thoracic surgery. Results. A total of 234 completed questionnaires were returned with a response rate of 39%, with the majority of responses received from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…14 Nevertheless, more patients were mobilized at 48 h post-admission and afterwards with the most commonly used techniques the active limb mobilization and transfer from bed to the chair which are consistent with other protocols. 18,17 Mobilization seemed to be beneficial for improving the outcomes of mechanically ventilated patients as also reported by Ding et al, 19 indicating the initiation of mobilization within 48-72 h of mechanical ventilation. However, there is little evidence on certified protocols and on how best to implement physiotherapy intervention.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…14 Nevertheless, more patients were mobilized at 48 h post-admission and afterwards with the most commonly used techniques the active limb mobilization and transfer from bed to the chair which are consistent with other protocols. 18,17 Mobilization seemed to be beneficial for improving the outcomes of mechanically ventilated patients as also reported by Ding et al, 19 indicating the initiation of mobilization within 48-72 h of mechanical ventilation. However, there is little evidence on certified protocols and on how best to implement physiotherapy intervention.…”
Section: Discussionmentioning
confidence: 54%
“…9,10,11 For safety concerns, it has been reported that is safe with an overall cumulative incidence of potential safety events of 2.6% and rare (0.6%) medical consequences. 12 Although there is a growing number of studies about physiotherapy intervention to ICU patients 13,14,7 and in particular after cardiac surgery, 15,16,17 the rates of early mobilization are controversial. There is a variety of physiotherapeutic techniques and time for launching early mobilization.…”
Section: Introductionmentioning
confidence: 99%
“…Dangling of lower limbs over edge of the bed was done in day one, walking up to chair and sit to stand exercises in day two and staircase climbing by day four. 23 In our study, we noted differences in minimally invasive and invasive approaches after step 6. As walking is commenced from step 6, postoperative pain in invasive approach might have limited progression from this step onwards.…”
Section: Minimally Invasive Invasivementioning
confidence: 57%
“…Physical therapy in the postoperative period of surgical procedures with sternotomy or thoracotomy aims at pulmonary reexpansion and mucociliary clearance [9]. In addition, attention should be paid to postural corrections, associated with the presence of the thoracic drain [10] and limitations of ROM, possibly related to the thoracic approach. When analyzing the joint range of motion, it was verified that only in the horizontal abduction of the right shoulder there was no statistically significant reduction (p = 0.08).…”
Section: Discussionmentioning
confidence: 99%